Development of KCC2 therapeutics to treat neurological disorders - Kadam, Shilpa D.; Hegarty, Shane V. (Frontiers in Molecular Neuroscience, 2024)
KCC2 is CNS neuron-specific chloride extruder, essential for the establishment and maintenance of the transmembrane chloride gradient, thereby enabling synaptic inhibition within the CNS. Herein, we highlight KCC2 hypofunction as a fundamental and conserved pathology contributing to neuronal circuit excitation/inhibition (E/I) imbalances that underly epilepsies, chronic pain, neuro-developmental/-traumatic/-degenerative/-psychiatric disorders. Indeed, downstream of both acquired and genetic factors, multiple pathologies (e.g., hyperexcitability and inflammation) converge to impair KCC2-dependent inhibition in CNS. When KCC2 hypofunction occurs, affected neurons are disinhibited due to impaired inhibitory responses to GABA/glycine. This causes neuronal hyperexcitability, disinhibition within neuron circuits, and disrupted neurological functions. More recently, KCC2 was identified as a genetically-validated target for epilepsy, intellectual disability, and autism spectrum disorder, and pathogenic mutations in human SLC12A5 gene were linked to psychiatric/mood disorders. The broad therapeutic utility of KCC2-upmodulating drugs relates to its critical role in determining inhibitory activity of GABAergic neurotransmission, a mechanism widely targeted by several drugs. However, in cases of KCC2 hypofunction GABAergic neurotransmission can be depolarizing/excitatory, thereby impairing endogenous neuronal inhibition while also limiting the effectiveness of existing therapeutics targeting/requiring GABAergic pathway inhibition. Several preclinical reports have shown that KCC2 upmodulating treatments rescue and increase the efficacy of anti-seizure and analgesic medications. Thus, a first-in-class KCC2-potentiating therapy would provide a novel mechanism for restoring physiological CNS inhibition and addressing drug resistance in patients with E/I imbalance pathologies. Herein, we discuss progress toward and further work needed to develop the first-in-class KCC2 therapeutics to treat neurological disorder patients.